Post cardiac surgery sternal wound sepsis burden, risk factors and outcomes at Red Cross War Memorial Children's Hospital, Cape Town, South Africa: a five-year experience - Mpisane, Fefekazi (Department of Paediatrics and Child Health, 2021)
Purpose Sternal wound infection (SWI) is associated with significant morbidity and mortality in postoperative cardiac patients. We aimed to describe the burden, risk factors and outcomes of SWI in post-operative paediatric cardiac patients at a tertiary children's hospital. Methods We conducted a retrospective record review of cardiac surgeries via median sternotomy over a five-year period to identify cases of SWI. Results Between 2012-16, 1319 patients underwent median sternotomy. Thirty-four (2.6%) patients developed SWI; eighteen (1.4%) patients developed deep sternal wound infection (DSWI), and sixteen (1.2%) developed superficial sternal wound infections (SSWI). Twenty-two (1.6%) of SWIs were apparent within a week post-surgery before discharge, the remaining were re-admitted post-discharge. Seven (0.5%) patients died from complications. Conclusion Significant morbidity was associated with SWI. Furthermore, with a mortality rate of 20 % in the case of DSWI. We strongly support quality improvement procedures such as the Sternal Wound Prevention Bundle (SWPB) that was introduced in late 2014. However, the rate of SWI implies that ongoing monitoring and evaluation of the SWPB is necessary and more stringent adherence to the protocol may result in better outcomes.